2018
DOI: 10.1104/pp.18.01228
|View full text |Cite
|
Sign up to set email alerts
|

A Golgi-Released Subpopulation of the Trans-Golgi Network Mediates Protein Secretion in Arabidopsis

Abstract: Spatiotemporal coordination of protein trafficking among organelles is essential for eukaryotic cells. The post-Golgi interface, including the trans-Golgi network (TGN), is a pivotal hub for multiple trafficking pathways. The Golgi-released independent TGN (GI-TGN) is a compartment described only in plant cells, and its cellular and physiological roles remain elusive. In Arabidopsis (Arabidopsis thaliana), the SYNTAXIN OF PLANTS (SYP) 4 group Qa-SNARE (soluble N-ethylmaleimide) membrane fusion proteins are sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 65 publications
3
101
0
Order By: Relevance
“…The TGN is divided into different functional domains that effectively sort cargo into different vesicles depending on their destination, facilitating the complex trafficking pathways originating at this organelle (Ladinsky et al, 2002;Dettmer et al, 2006;Toyooka et al, 2009;Viotti et al, 2010;Singh et al, 2014;Renna et al, 2018). The TGN has been proposed to mature and be released from its association with the Golgi, generating an independent compartment that can deliver material to the plasma membrane (Viotti et al, 2010;Uemura et al, 2014Uemura et al, , 2019. Different coat proteins, soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), tethering factors and lipids appear to define different subdomains of the TGN (Bassham et al, 2000;Chow et al, 2008;Gendre et al, 2011;Wattelet-Boyer et al, 2016;Renna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The TGN is divided into different functional domains that effectively sort cargo into different vesicles depending on their destination, facilitating the complex trafficking pathways originating at this organelle (Ladinsky et al, 2002;Dettmer et al, 2006;Toyooka et al, 2009;Viotti et al, 2010;Singh et al, 2014;Renna et al, 2018). The TGN has been proposed to mature and be released from its association with the Golgi, generating an independent compartment that can deliver material to the plasma membrane (Viotti et al, 2010;Uemura et al, 2014Uemura et al, , 2019. Different coat proteins, soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), tethering factors and lipids appear to define different subdomains of the TGN (Bassham et al, 2000;Chow et al, 2008;Gendre et al, 2011;Wattelet-Boyer et al, 2016;Renna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that SNARE proteins likely function in trafficking at most membranes, but especially at the vacuole and plasma membrane. And VAMP727 forms a complex with SYP22, VTI11, vacuoles [32,33,104]. Löfke et al [88] found that auxin can increase the amount of SNARE proteins in the vacuolar membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The four VAMP71 group proteins are involved in endosomal trafficking [10,24]; while the eight VAMP72 group proteins are likely specific to the green plant lineage and represents R-SNARE components involved in secretion [12,19]. VAMPs have roles as key proteins in abiotic stress tolerance (VAMP711, VAMP712) [25,26], in gravitropic responses [27], in cell plate formation (VAMP721, VAMP722) [28][29][30][31][32][33], in cytokinesis [29,34], in defence responses [28,31,35], in the transport of phytohormones (e.g. abscisic acid, ABA and auxin) and in root formation and hormone response in plants [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…For functional analysis of SYP12s related SNAREs, different SNARE mutants were generated and the extracellular proteomes assessed [60]. Overall, pathogen-inducible protein secretion changes were observed in all mutants except syp42syp43vamp721.…”
Section: The Golgi Apparatus and The Trans-golgi Network/early Endosomentioning
confidence: 99%
“…This finding suggests that targeted protein secretion at sites of fungal contact on the leaf epidermal surface depends on the SYP4-VAMP721 secretory pathway. Taken into account that apoplastic fluids from leaves are possibly dominated by proteins secreted from mesophyll cells (not having direct contact with the pathogen), it has been suggested that the SYP4-VAMP721 pathway also contributes to a systemic cell wall remodeling response [60]. In recent years, it became evident that Rab GTPases also plays an important role in plant immunity.…”
Section: The Golgi Apparatus and The Trans-golgi Network/early Endosomentioning
confidence: 99%